2014
DOI: 10.1016/j.jvs.2014.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions after complex aneurysm repair are frequent, costly, and primarily at nonindex hospitals

Abstract: Early readmissions after TAA/TAAA repair are frequent and often occur at hospitals other than the index institution. Risk factors for readmission include open repair and postoperative pneumonia but not pre-existing patient comorbidities. Readmissions to nonindex hospitals were related to medical morbidities that were associated with fewer interventions and lower costs compared with the index hospital. Focusing on preoperative risk factors in this group of patients may not lead to reduction in readmissions. Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…1416,18,25,37 Our study suggests that although non-index readmission is associated with higher in-hospital mortality, this increase might be attributable to varying clinical conditions leading to readmissions at different locations. Similarly, a hospital-level analysis from New York state also found that although the aggregate 30-day mortality rate was higher at non-index hospitals than index hospitals after radical cystectomy, this elevation was mitigated by adjustment of covariates, including severity of illness and risk of mortality, which both captured all patient refined diagnosis-related group and diagnoses at readmission.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…1416,18,25,37 Our study suggests that although non-index readmission is associated with higher in-hospital mortality, this increase might be attributable to varying clinical conditions leading to readmissions at different locations. Similarly, a hospital-level analysis from New York state also found that although the aggregate 30-day mortality rate was higher at non-index hospitals than index hospitals after radical cystectomy, this elevation was mitigated by adjustment of covariates, including severity of illness and risk of mortality, which both captured all patient refined diagnosis-related group and diagnoses at readmission.…”
Section: Discussionmentioning
confidence: 77%
“…13 It was reported that among those readmitted after major cancer surgery, 22% to 79% are readmitted to a hospital other than that where the index cancer surgery was performed. 1,7,1418 Such non-index readmissions constitute a form of care fragmentation and challenge care coordination between index and readmitting hospitals. 18 Despite the ponderous evidence from medical research that associates provider continuity with better patient outcomes and provider fragmentation with lower quality of care and higher costs, 19–22 this hypothesis has not been sufficiently tested in postoperative settings.…”
mentioning
confidence: 99%
“…This finding has also been reported with readmissions after complex vascular surgery, in which readmissions related to medical comorbidities were more likely to be to nonindex hospitals. 21 High-acuity conditions often generate a call to an ambulance that will invariably take the patient to the closest hospital. These patients often require early stabilization, and transport to the nearest hospital may be the most appropriate measure at the time.…”
Section: Discussionmentioning
confidence: 99%
“…This improves the accuracy and validity of the readmitted patients cohort compared with claims data [22]. In addition, the ACS NSQIP PUF records the reason for readmission, which helps distinguish between related and unrelated and planned and unplanned readmissions [23].…”
Section: Commentmentioning
confidence: 99%